Should welfare administration be centralized or decentralized? Evidence from a policy experiment - Bernhard Boockmann; Stephan L. Thomsen; Thomas Walter; Christian Göbel; Martin Huber (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
The 2005 reform of the German welfare system introduced two competing organizational models for welfare administration. In most districts, a centralized organization was established where local welfare agencies are bound to central directives. At the same time, 69 districts were allowed to opt for a decentralized organization. We evaluate the relative success of both types of organizations. Compared to centralized organization, decentralized organization of welfare administration has a negative effect on the transition of male welfare recipients to self-sufficient employment, but it does not affect employment in combination with continuing welfare support. No significant effects were found for women.
Keywords: I38; J64; C31; 330; Welfare System; Organization; Decentralization; Labor Market Integration; Sozialverwaltung; Arbeitsverwaltung; Dezentrale Organisation; Wirkungsanalyse; Berufliche Integration; Schätzung; Deutschland